Marshall Plan, 1947 (pg. 1) (1947)
1947 1945-1960 "Marshall Plan, 1947 (pg. 1)" [HFR0105a], 1947 In 1947, the American Secretary of State, George Marshall, proposed his European Recovery Programme, later known as the Marshall Plan, to rebuild a war-shattered Europe. Marshall offered financial aid from the USA for a programme of European economic recovery. In April 1948, President Harry S. Truman signed the first appropriation bill authorizing $5,300,000,000 for the first year. The European Recovery Program came to an end on 31 December, 1951. In its three year existence, the ERP spent almost $12,500,000,000, with Britain receiving the largest share of any European nation.